Leptin Is Required for Glucose Homeostasis after Roux-en-Y Gastric Bypass in Mice - Mokadem, Mohamad (PLoS One, 2015)
BACKGROUND & AIMS: Leptin, the protein product of the ob gene, increases energy expenditure and reduces food intake, thereby promoting weight reduction. Leptin also regulates glucose homeostasis and hepatic insulin sensitivity via hypothalamic proopiomelanocortin neurons in mice. Roux-en-Y gastric bypass (RYGB) induces weight loss that is substantial and sustained despite reducing plasma leptin levels. In addition, patients who fail to undergo diabetes remission after RYGB are hypoletinemic compared to those who do and to lean controls. We have previously demonstrated that the beneficial effects of RYGB in mice require the melanocortin-4 receptor, a downstream effector of leptin action. Based on these observations, we hypothesized that leptin is required for sustained weight reduction and improved glucose homeostasis observed after RYGB. METHODS: To investigate this hypothesis, we performed RYGB or sham operations on leptin-deficient ob/ob mice maintained on regular chow. To investigate whether leptin is involved in post-RYGB weight maintenance, we challenged post-surgical mice with high fat diet. RESULTS: RYGB reduced total body weight, fat and lean mass and caused reduction in calorie intake in ob/ob mice. However, it failed to improve glucose tolerance, glucose-stimulated plasma insulin, insulin tolerance, and fasting plasma insulin. High fat diet eliminated the reduction in calorie intake observed after RYGB in ob/ob mice and promoted weight regain, although not to the same extent as in sham-operated mice. We conclude that leptin is required for the effects of RYGB on glucose homeostasis but not body weight or composition in mice. Our data also suggest that leptin may play a role in post-RYGB weight maintenance.